A chlorophyll halo over maud rise in the southern ocean - Ducrocq, Bertrand; Steiger, Nadine; du Plessis, Marcel; Sallée, Jean-Baptiste; Moreau, Sébastien; Swart, Sebastiaan (Nature communications, 2025)
Phytoplankton blooms above the seamount Maud Rise in the Antarctic Ocean have been reported but their emerging mechanisms and their importance for the wider Southern Ocean are not well known. We use satellite data spanning over the last two decades and in-situ data collected from a ship, an underwater glider and Biogeochemical-Argo profiling floats to understand the processes involved in the formation of Maud Rise phytoplankton blooms. We find that the seamount generates upwelling of warm deep water that transports heat, and likely dissolved iron, to the surface via diapycnal mixing. This creates a recurring annular structure of chlorophyll concentration (or chlorophyll halo) in correspondence with the previously observed warm water and sea ice halo over Maud Rise. The in-situ observations reveal integrated chlorophyll-a concentrations of up to 100 mg·m(-2), which suggests exceptionally high phytoplankton biomass within the Southern Ocean, thus making the seamount a regional phytoplankton hotspot.
Place: England
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; oseanografi